The functional performance of engineered cementitious composites material for electrified roadway application in Singapore - Ali Aryo Bawono (Nanyang Technological University, 2021)
The concept of electrified roadway for wireless inductive charging of electric vehicles (EVs) was proposed as a solution for electromobility to achieve an ultimate public transport system. In megacities such as Singapore, in order to reduce construction time and to minimize road closure duration, a new pavement system named Precast Ultra-thin Whitetopping (PUTW) was developed for rapid retrofitting and conversion of existing road infrastructure into electrified roadways. Engineered Cementitious Composite (ECC) is a high-performance fiber-reinforced cementitious composite exhibiting extreme tensile strain capacity several hundred and flexural strength 2-3 times that of normal concrete. These enable the design of PUTW for electrified roadway as the thickness of whitetopping can be greatly reduced without the need for steel reinforcement as reinforcement can cause interference of electromagnetic field of inductive charging and lead to reduction of charging efficiency. However, due to the omission of coarse aggregates in ECC mix design, pavement made of ECC generally shows low skid resistance which might cause skid-accidents in highway traffic. On top of that, high intensity of rainfall might increase the risk of hydroplaning which also leads to wet-skid accident. It is challenging to study the functional performance of a surface pavement with new material without learning the existing solutions. Therefore, a method to study the functional performance from existing surface treatments has been developed. The optimum solution is then defined based on Multi-Criteria Design Analysis (MCDA) including, microtexture, macrotexture, pavement drainage (splash and spray), pavement unevenness, noise, cost, and durability. The understanding acquired is then used as a foundation for the study. The scope of the study is focused on the functional performance of pavement made of the modified ECC material, especially on the safety aspect. The ECC is modified with fine aggregates, corundum (ECC-Cor) and silica sand (ECC-SS), to improve the surface texture. As for the safety-related functions, the skid resistance and surface water drainage are deeply studied with the laboratory experiments and numerical tools validated with field tests. Additionally, the tyre-road noise for ECC-Cor has been measured and analyzed with numerical tools. The ECC is then further improved for future-green-infrastructure for better liveability in megacities. The ECC is modified with bright color fine aggregates silica sand, called ECC-SS, and carbon modified Ti¬O2 to engage self-cleaning functions. The resulting ECC-Cor possesses satisfactory mechanical performance (i.e., compressive strength > 50 MPa, tensile strength > 4.5 MPa, and tensile strain capacity > 4%) and high skid resistance (BPN > 70). ECC-Cor also shows good durability. Further surface treatment with grooves capable in minimizing the risk of hydroplaning (water outflow time < 4 s) but also by improving the skid resistance (BPN > 90). The sound level of ECC-Cor is higher than ECC (69.2 dB > 64.6 dB). However, with modification by introducing grooves, the sound level can be reduced to less than 65 dB. ECC-SS produces high surface reflectivity with a brightness value of 90. Furthermore, it shows strong visible-light activated photocatalysis property with 90% reflectance recovery after 4 h visible light irradiation and only 8% surface brightness reduction after the accelerated dirt pick-up resistance test. In summary, this study is highly important as it can be used as the foundation for other studies in relation to the modification of fiber based cementitious material for pavement application, both for electrified and normal roadways. In particular in tropical megacities.